IMPLEMENTASI KEBIJAKAN STANDAR OPERASIONAL PROSEDUR PADA PENERIMAAN PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT MANADO - RARES, JOYCE JACINTA; RURU, JOORIE MARHAEN; MA’RUF, FEISAL (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRACT : The purpose of this research to see how of policy implementation SOP on PKB in the office of SAMSAT Manado. Revenue, the collection or tax management motor vehicle is performed at one an office that involves agencies in it work together between the police of the republic of Indonesia (POLRI) that have function, and authority in registration and identification motor vehicle, the local government to this department of local revenue (DISPENDA) in tax collection of motor vehicles and BBN-KB, PT. Jasa Raharja (persero) authorities in the delivery of compulsory contributions funds traffic accident the way (SWDKLLJ). Because there were three agencies who are served in SAMSAT the process of the implementation policy is held up on the bureaucratic structure, communication, disposition, and human resources/mental owned by officers/ASN to serve the people. For example, when of obtaining has been completed in the local treasury office (DISPENDA) but be stunted in Police, so also on the other hand. This research is descriptive with a qualitative approach interactive. The research uses guidelines, observation and study documentation with informants research as much as 8 (eight) a person, including 5 (five) officials SAMSAT Infroman keys is head technical unit agency (UPTB) and The Department PKB service, bea balik the vehicle motor (BBN-KB), surface water tax (PAP); and 3 (three) a person of the community/people or an applicant tax who takes care of PKB. The conclusion of the research indicated that in general the implementation of policies in SOP on state revenues PKB served in SAMSAT Manado already has worked fairly well, but has not yet been optimized. This can be seen from SAMSAT officers who have not socialize the standart time, and the cost of motor vehicle taxes, and the lack of facilities in obtaining motor vehicle taxes. Advice can be given at this research is of implementation policy SOP on state revenues or SAMSAT Manado on the communication, disposition, resources and bureaucratic structure have generally been it can be said is good, but the system and legal procedures for obtaining motor vehicle tax ongoing between counter needs to be simplified for his ministry more practical and efficien.Keywords : Implementation Policy SOP, Motor Vehicle Tax, SAMSAT Manado.